THE EFFECTIVENESS OF THE TREATMENT OF INITIAL DENTAL CARIES IN CHILDREN BY THE METHOD OF CARIES INFILTRATION (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In children, carious defects in permanent teeth are often formed against the background of focal demineralization of the teeth. Traditional caries treatment involves the complete removal of enamel with signs of demineralization. This approach to treatment led to significant loss of hard tissue and weakening of the supporting structures of the teeth. Currently, focal demineralization of enamel is being treated by remineralizing therapy or fluorization. However, this approach requires multiple visits and does not guarantee good results, especially when patients are poorly competent to follow the recommendations for brushing teeth, nutrition, and the use of flossids. The article presents the results of treatment of children with focal demineralization of enamel on permanent teeth. The topographic features of the location of focal demineralization of enamel on the vestibular surfaces of the teeth were determined. Described is the technique of demineralized enamel infiltration technology in combination with rational oral hygiene, which makes it possible to “conserve” the carious process in one visit, provided that the pseudo-intact enamel layer is preserved. The study revealed a high caries-static efficiency of the ICON technology infiltration method due to adequate sealing of pores in the demineralization focus.